2006
DOI: 10.7155/jgaa.00122
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Hypergraph Drawing for Improved Visibility

Abstract: Visualization of circuits is an important research area in electronic design automation. One commonly accepted method to visualize a circuit aligns the gates to layers and uses orthogonal lines to connect the gates. In our model we assume that between two consecutive layers every net is allowed to occupy only one track. This avoids unnecessary bends in the wires and helps to improve the clarity of the drawing. Then a crossing reduction step is applied to further improve the readability of the circuit schematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
0
18
0
2
Order By: Relevance
“…Other unpublished solutions to drawing with port constraints include ILOG JViews [18] and Tom Sawyer Visualization 4 . Handling of hyperedges in hierarchical layout has been covered by Eschbach et al [10] and Sander [17]. Sugiyama et al [21] and Sander [16] showed how to draw general compound graphs, but due to the presence of external ports (see Section 2), our requirements for compound graphs are different.…”
Section: Port Constraints and Hyperedgesmentioning
confidence: 99%
See 3 more Smart Citations
“…Other unpublished solutions to drawing with port constraints include ILOG JViews [18] and Tom Sawyer Visualization 4 . Handling of hyperedges in hierarchical layout has been covered by Eschbach et al [10] and Sander [17]. Sugiyama et al [21] and Sander [16] showed how to draw general compound graphs, but due to the presence of external ports (see Section 2), our requirements for compound graphs are different.…”
Section: Port Constraints and Hyperedgesmentioning
confidence: 99%
“…Although there are approaches to directly handle hyperedges [10,17], we split all hyperedges into sets of plain edges in order to simplify the algorithms. For this reason we consider all edges that are incident at the same port of a vertex as parts of a single hyperedge.…”
Section: Port Constraints and Hyperedgesmentioning
confidence: 99%
See 2 more Smart Citations
“…In relational databases there is a natural correspondence between database schemata and hypergraphs, with attributes corresponding to vertices and relations to hyperedges [7]. Hypergraphs are used in VLSI design for circuit visualization [6,14] and also appear in computational biology [10,12] and social networks [3].…”
Section: Introductionmentioning
confidence: 99%